2016
DOI: 10.1177/0021998316661870
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nano-silica/nano-alumina on fatigue behavior of glass fiber-reinforced epoxy composites

Abstract: This paper presents an experimental and statistical study of the fatigue behavior of unidirectional glass fiber-reinforced epoxy composite rods manufactured using pultrusion technique and modified with nanoparticles of alumina (Al2O3) and silica (SiO2) at four different weight fractions (0.5, 1.0, 2.0 and 3.0 wt.%). Tensile test was performed to investigate the influence of nanoparticles. Addition of alumina nanoparticles up to 3 wt.% increases the tensile strength by 54.76% over the pure glass fiber-reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…Significant enhancement in fracture toughness of the matrix system was observed in various cases through key toughening mechanisms like crack pinning, crack deflection, crack bridging, and filler debonding [7,8]. Researchers endeavored to use nanofillers, like single-walled carbon nanotubes (SWCNT), double- walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT) [9,10,11,12], graphene [13,14,15], nanoclay [16,17,18], and nanosilica [19,20,21] into various polymers and reported the effect of reinforcement in polymer composites. However, reinforcing nanofillers into the polymer matrix does not always enhance the fracture toughness and modulus of the composite material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant enhancement in fracture toughness of the matrix system was observed in various cases through key toughening mechanisms like crack pinning, crack deflection, crack bridging, and filler debonding [7,8]. Researchers endeavored to use nanofillers, like single-walled carbon nanotubes (SWCNT), double- walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT) [9,10,11,12], graphene [13,14,15], nanoclay [16,17,18], and nanosilica [19,20,21] into various polymers and reported the effect of reinforcement in polymer composites. However, reinforcing nanofillers into the polymer matrix does not always enhance the fracture toughness and modulus of the composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [19] synthesized nanosilica fillers of 80 nm by a sol-gel technique and achieved a homogeneous dispersion through mechanical blending and enhanced interfacial bonding between glass fiber and modified epoxy. Fathy et al [20] synthesized silica nanoparticles of a size in the order of 10–20 nm and examined the fatigue performance of nanosilica-reinforced glass fiber composite laminates. Johnsen et al [21] investigated the influence of nanofillers of different sizes as toughening agents and also explored the associated toughening mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosilica is identified as a new potential candidate material for secondary reinforcement as it occupies the tiniest voids and enhances the interfacial binding of the fibers in the laminates which results in substantial stress transfer. A few research activities using nanosilica as secondary reinforcement is reported in [31,32,33]. Gong et al [31] synthesized silica nano fillers of size 80 nm by sol gel technique.…”
Section: Introductionmentioning
confidence: 99%
“…They successfully achieved homogeneous dispersion using mechanical blending and reported enhanced interfacial bonding between glass fibre and modified epoxy. Fathy et al [32] synthesized silica nano particle of size 10–20 nm and investigated the fatigue behaviour of nano silica reinforced glass fibre composite laminates. Johnsen et al [33] studied the effect of nano fillers of different sizes as toughening agents and explored the associated toughening mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been suggested in the survey for the preparation of copper matrix composites like stir casting [29], traditional powder metallurgy [30][31][32], hot press [33], friction stir processing (FSP) [34,35], infiltration [36] and spark plasma sintering (SPS) [37,38]. Casting method is a suitable technique for enhancing mechanical characteristics; however, hard in dominant mixing the constituents [39].…”
Section: Introductionmentioning
confidence: 99%